Adult teaching and learning theory: a psychoanalytic investigation - Davies, Lindsay (2010)
The overarching aim of this thesis is to enhance the theoretical status of post-compulsory education by effecting a non-empirical, psychoanalytic examination of adult teaching and learning theories. The study arises out of the observation that – in comparison with disciplines within the Social Sciences, Arts and Humanities - psychoanalytic perspectives are both underemployed in practical contexts and have negligible theoretical impact within this field.